The Use of the Saud Model (Start, Action, Utilization, Destination) Assisted by Fishbone Diagram Media to Improve Language Rules Mastery in Expository Text Writing Among Phase E Students - Dheni Harmaen; Sintia Daniati; Lili Sadeli (Global Action and Education for Society, 2025)
This study aims to determine the effectiveness of implementing the SAUD model (Start, Action, Utilization, Destination) assisted by fishbone diagram media in improving the mastery of language rules in expository text writing among Phase E students at SMA Pasundan 7 Bandung. This research employed a descriptive quantitative method with a One-Group Pretest–Posttest Design. The sample consisted of Phase E students at SMA Pasundan 7 Bandung. Data collection techniques included the N-Gain test to measure the effectiveness of the model and media. Based on the research findings, it can be concluded that the use of the SAUD model assisted by fishbone diagram media is effective in enhancing students’ mastery of language rules in expository writing. This is supported by the N-Gain test results, which showed a score of 72.8910 or 72%, categorized as moderately effective, with an N-Gain range between 1% and 100%. The minimum pretest score was 26 and the maximum was 86, while the posttest scores ranged from 73 to 100.